THE EFFECT OF MULTIPLE ROLE CONFLICT AND JOB STRESS ON EMPLOYEE PERFORMANCE - Irsan Tricahyadinata; Rizki Fakhrowan (Social Sciences, Humanities and Education Journal (SHE Journal), 2022)
The Influence of Dual Role Conflict and Stress on the Performance of Female Employees at the Department of Population and Civil Registration Samarinda. Guidance Irsan Tricahyadinata as supervisor I and Alexander Sampleiling as supervisor II. This study aims to explain the effect of dual role conflict and work stress on the performance of female employees at the Department of Population and Civil Registration Samarinda. This research was conducted at government agencies in Samarinda. The sampling method used the saturated method. The analysis technique in this study uses the Partial Least Square (PLS) data analysis method. The results of the analysis show that multiple role conflicts have a positive and significant effect on the performance of female employees, multiple role conflicts have a positive and significant effect on work stress, job stress has a positive and significant effect on the performance of female employees, and multiple role conflicts have a positive and insignificant effect on the performance of female employees. through work stress as a mediating variable